Sex differences in physical fitness among 10,000 adolescents aged 13–15 years - Ali Gorzi; Hamid Rajabi; Mina Khantan; Tommy R. Lundberg (PLoS ONE, 2026)
Physical fitness during adolescence is critical for health and sports participation, with sex-specific developmental trajectories influencing performance. The aim of this cross-sectional study was to examine sex differences in physical fitness among non-athletic adolescents aged 13–15 years and to provide reference values for fitness parameters across age and sex. We assessed 9,669 non-athletic adolescents (64% females) aged 13–15 years. Fitness tests included Sargent jump, standing long jump, 30m sprint, medicine ball chest throw, and 6-minute shuttle run. Interactions between sex and age were analyzed using two-way ANOVA, with effect sizes (Cohen’s d ) and mean differences calculated between 13–15 years of age. Pearson correlation coefficients were used to examine relevant relationships, and were compared between sexes using Fisher’s r-to-z transformation. Significant sex-by-age interactions were observed for all fitness parameters (p < 0.001). Boys showed greater differences than girls from 13 to 15 years, with mean differences for Sargent jump (7.0 vs. 1.6 cm), standing long jump (28 vs. 7 cm), 30m sprint (−0.54 vs. −0.01 s), medicine ball throw (1.6 m vs. 0.4 m), and 6-minute shuttle run (2.0 vs. −0.3 laps). Height correlated moderately with the power-based tests in both sexes (p < 0.001), particularly in boys (R = 0.21 to 0.56 depending on age and test), but not with endurance. Correlations between tests were stronger (p < 0.01) in boys for all comparisons except medicine ball throw vs. shuttle run. We conclude that boys show larger fitness differences from 13 to 15 years of age than girls, likely due to pubertal changes that increase stature and improve muscle mass and body composition. These reference values serve as a basis for sex-specific interventions to improve adolescent health, performance, and sports participation.